Histological basis of laminar MRI patterns in high resolution images of fixed human auditory cortex - Wallace, Mark N.; Cronin, Matthew John; Bowtell, Richard W.; Scott, Ian; Palmer, Alan R.; Gowland, Penny A. (Frontiers Media, 2016)
Functional magnetic resonance imaging (fMRI) studies of the auditory region of the temporal lobe would benefit from the availability of image contrast that allowed direct identification of the primary auditory cortex, as this region cannot be accurately located using gyral landmarks alone. Previous work has suggested that the primary area can be identified in magnetic resonance (MR) images because of its relatively high myelin content. However, MR images are also affected by the iron content of the tissue and in this study we sought to confirm that different MR image contrasts did correlate with the myelin content in the grey matter and were not primarily affected by iron content as is the case in the primary visual and somatosensory areas. By imaging blocks of fixed post-mortem cortex in a 7 Tesla scanner and then sectioning them for histological staining we sought to assess the relative contribution of myelin and iron to the grey matter contrast in the auditory region. Evaluating the image contrast in T2*-weighted images and quantitative R2* maps showed a reasonably high correlation between the myelin density of the grey matter and the intensity of the MR images. The correlation with T1-weighted phase sensitive inversion recovery (PSIR) images was better than with the previous two image types, and there were clearly differentiated borders between adjacent cortical areas in these images. A significant amount of iron was present in the auditory region, but did not seem to contribute to the laminar pattern of the cortical grey matter in MR images. Similar levels of iron were present in the grey and white matter and although iron was present in fibres within the grey matter, these fibres were fairly uniformly distributed across the cortex. Thus we conclude that T1- and T2*-weighted imaging sequences do demonstrate the relatively high myelin levels that are characteristic of the deep layers in primary auditory cortex and allow it and some of the surrounding areas to be reliably distinguished.